Hypercylindrical art - Bica, Ion (My University, 2022)
Every form and shape that surrounds us has a purpose, and mathematics helps in understanding it. Mathematics provides a source of abstract forms, i.e., mathematical structures, which are deliberately emptied of any content and therefore adaptable to any content. Art History is a testimony of great artists who adapted abstract mathematical forms, giving them artistic content. The article was inspired by a piece of art that I purchased of a talented emerging Ecuadorian artist, Tanya Zevallos. Her “Cylindrical Abstract Construction #124” artwork inspired me to look at the mathematical perspective that she gave in her art and construct further abstract aesthetics using cylinders.
Keywords: art; mathematics; cylinders